Amenazas asociadas a virus emergentes que infectan papaya en Argentina - Cabrera Mederos, Dariel; Portal, Orelvis; Sáez, S.; Silva, Milagros Itatí; Brugo Carivali, María Florencia; Trucco, Veronica Milagros; Ortiz, Claudio Manuel; Fernandez, Franco Daniel; Luciani, Cecilia Elizabeth; Celli, Marcos Giovani; Perotto, Maria Cecilia; Castellanos Collazo, Onias; et al. (Centro Nacional de Sanidad Agropecuaria (CENSA), Cuba, 2024)
Poster y resumen